2017
DOI: 10.1111/1462-2920.13676
|View full text |Cite
|
Sign up to set email alerts
|

Permeability shapes bacterial communities in sublittoral surface sediments

Abstract: The first interaction of water column-derived organic matter with benthic microbial communities takes place in surface sediments which are acting as biological filters catalyzing central steps of elemental cycling. Here we analyzed the bacterial diversity and community structure of sediment top layers at seven sites in the North Sea where sediment properties ranged from coarse-grained and highly permeable to fine-grained and impermeable. Bacterial communities in surface sediments were richer, more even and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 87 publications
9
52
0
Order By: Relevance
“…5a, Table S3). Cells of Woeseiales bacteria accounted for 1-9% of all cells detected by DAPI staining (5 ± 3%, Table S3), similar to proportions reported from tidal (3-6% [6]) and sublittoral coastal sandy sediments (1-6% [9]). For comparison, Gammaproteobacteria accounted for 1-25% of DAPIstained cells in the surveyed deep-sea sediments with the exception of a single sediment sample (site AO.5c in Fram Strait; 4-5 cm below the seafloor surface) where they accounted for up to 67% of DAPI-stained cells (Table S3 and Supplementary text 13).…”
Section: Abundance Of Woeseiales Bacteria In the Deep Seasupporting
confidence: 78%
See 1 more Smart Citation
“…5a, Table S3). Cells of Woeseiales bacteria accounted for 1-9% of all cells detected by DAPI staining (5 ± 3%, Table S3), similar to proportions reported from tidal (3-6% [6]) and sublittoral coastal sandy sediments (1-6% [9]). For comparison, Gammaproteobacteria accounted for 1-25% of DAPIstained cells in the surveyed deep-sea sediments with the exception of a single sediment sample (site AO.5c in Fram Strait; 4-5 cm below the seafloor surface) where they accounted for up to 67% of DAPI-stained cells (Table S3 and Supplementary text 13).…”
Section: Abundance Of Woeseiales Bacteria In the Deep Seasupporting
confidence: 78%
“…In these studies, members of this group account for 1-22% of the sequences retrieved. Cell counts in coastal sediments have indicated that these bacteria account on average for 6% of the surveyed microbial communities [6,8,9], yet their cell densities in deep-sea sediments remained unknown. Notably, distinct lineages within JTB255-MBG were detected in coastal and deep-sea sediments, suggesting that certain taxa within this group occur in specific types of environments, i.e., in either deep-sea or coastal environments [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such a heterotrophic oxidation of H 2 is widespread among SRM (Rabus et al ., ) and is in line with very low CO 2 assimilation rates measured in sulfidic sediment layers at site Janssand (Lenk et al ., ). The Sva0081‐MBG accounted not only for a major fraction of all SRM‐related 16S rRNA genes in our study, but also made up the dominant fraction of 16S rRNA gene amplicons of SRM in other coastal sediments (Wang et al ., ; Zheng et al ., ; Liu et al ., ; Probandt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, between 5% and 8% of 16S amplicon sequences derived from the upper layers of the sediment in the Wadden Sea are assigned to Flavobacteriia of which the genus Eudoraea were the most abundant single group (Dyksma et al, 2016). Similarly in subtidal sandy sediments from the German Bight, Flavobacteriia were very abundant (Probandt et al, 2017). Furthermore, Muricauda sp.…”
Section: Production and Consumption Of Denitrification Intermediates mentioning
confidence: 99%